Dynamic Strength and Anisotropy of Dmls Manufactured Maraging Steel - Eva Schmidova; Premysl Hojka; Bohumil Culek; Filip Klejch; Michal Schmid (Communications - Scientific letters of the University of Zilina, 2019)
This paper deals with maraging steel, as a prospective material for the 3D printed lightened structural parts of transport means. Direct Metal Laser Sintering technology was tested for creation of a thin-wall structure with defined internal geometry. The referential samples prepared by the DMLS technology were examined under quasi-static and high strain rate loading using a servo-hydraulic testing machine at strain rates up to 1400 s-1. Microstructural analyses served for evaluation of structural homogeneity and metallurgy quality, including the influence of crystallization gradient. The stabile ductile fracture mode was proven by fractography analyses, even at a maximal strain rate. The post-impact tests were conducted to evaluate the local residual plasticity by indentation tests.